The Influence Of Work Quality And Organizational Support On Employee Work Productivity At The Bengkulu Province Social Service - Febri Sukmawati; Sri Ekowati (Jurnal Fokus Manajemen, 2026)
This study aims to determine the effect of Work Quality and Organizational Support on Employee Work Productivity at the Bengkulu Province Social Service Office. The type of research used is descriptive quantitative research. The population in this study consists of all employees of the Bengkulu Province Social Service Office, with the sampling technique using the total sampling method. Data collection techniques were carried out through observation, interviews, and the distribution of questionnaires. The data analysis techniques used include descriptive analysis, multiple linear regression analysis with the assistance of the SPSS program, and analysis of the coefficient of determination (R²). The results of the study indicate that Work Quality has a positive and significant effect on the Work Productivity of Employees at the Bengkulu Province Social Service Office. This indicates that the better the Work Quality possessed by employees, the higher the level of Work Productivity produced. Organizational Support also has a positive and significant effect on Employee Work Productivity, which means that the higher the support provided by the organization to employees, the more optimal their performance and productivity. Simultaneously, Work Quality and Organizational Support have a positive and significant effect on Employee Work Productivity at the Bengkulu Province Social Service Office, indicating that a combination of good Work Quality and adequate Organizational Support can improve overall Work Productivity.